2021
DOI: 10.1111/hepr.13650
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy and safety of entecavir and switching from entecavir to tenofovir alafenamide fumarate in chronic hepatitis B: Long‐term effects from a prospective study

Abstract: Aim: Both entecavir (ETV) and tenofovir alafenamide fumarate (TAF) are widely used to treat chronic hepatitis B (CHB) in Japan. However, it remains unclear whether the efficacy of TAF in decreasing the hepatitis B surface antigen (HBsAg) level, and its safety, are superior to those of ETV. This study aimed to report the long-term effects and safety of 96-week ETV and TAF treatment in patients with CHB.Methods: A prospective comparative observational study was undertaken on the following two groups: patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
2
11
1
Order By: Relevance
“…Half of the patients with ETV experience were switched to TAF in a study, and the groups were compared. No significant difference was found between the two groups after 24, 48, and 96 weeks in serum HBsAg levels (22,23). In our study, the median duration of TDF treatment for those with detectable HBV-DNA at baseline was 12 months.…”
Section: Discussioncontrasting
confidence: 49%
“…Half of the patients with ETV experience were switched to TAF in a study, and the groups were compared. No significant difference was found between the two groups after 24, 48, and 96 weeks in serum HBsAg levels (22,23). In our study, the median duration of TDF treatment for those with detectable HBV-DNA at baseline was 12 months.…”
Section: Discussioncontrasting
confidence: 49%
“…Similar results were also reported by Itokawa et al [20], Li ZB et al [21], and Tamaki N, et al [22]. There were limitations of these studies, e.g., small study sample sizes [18,19,21,22], short TAF administration period (24 weeks) [21], and different sites of measurement of the serum HBsAg levels [17,20]. Thus, in the present study, we compared the degrees of reduction of the serum HBsAg levels over the long term (144 weeks) in the same cohort of patients as in our previous study [11], by comparison of the level between the 144-week ETV treatment period prior to switching of the nucleos(t)de analog from ETV to TAF and the 144-week TAF treatment period after the drug switching.…”
Section: Discussionsupporting
confidence: 85%
“…Kumada T, et al reported results similar to ours [11] in patients in whom the nucleos(t)ide analog used for treatment was switched from ETV to TAF [16]; on the other hand, Ogawa E, et al [17] did not find any superiority of TAF over ETV, in terms of the efficacy of the drugs in reducing the serum HBsAg levels. Moreover, Hagiwara et al reported similar degrees of reduction of the serum HBsAg level between patients in whom the nucleos(t)de analog was switched from ETV to TAF and those who had received ETV monotherapy [18,19]. Similar results were also reported by Itokawa et al [20], Li ZB et al [21], and Tamaki N, et al [22].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In the past decade, the etiologies of liver cirrhosis have changed 4 . The contribution of viral hepatitis as an etiology of liver cirrhosis has decreased due to advances in antiviral therapies 5–8 . In contrast, alcohol‐related liver disease and nonalcoholic steatohepatitis (NASH) have increased due to lifestyle changes 9–11 .…”
Section: Introductionmentioning
confidence: 99%